PENGARUH PENGETAHUAN TEKNIS, KOMITMEN MANAJEMEN, DAN SUMBER DAYA TERHADAP KUALITAS PENGUKURAN KINERJA PEMERINTAH DAERAH - Hakim, Moch Lukmanul; Rahayu, Agus; Wibowo, Lili Adi; Sugiharto, Moch. Dudih (JURISMA : Jurnal Riset Bisnis & Manajemen, 2021)
Performance measurement of local government in Indonesia needs to be improved as demanded by the central government. Based on institutional theory, there are three factors that influence the quality of local government performance measurement, namely technical knowledge, management commitment, and resources. This study examines the effect of those factors on the quality of local government performance measurements in the province of West Java. Respondents in this study were the head of regional government agency. Using PLS-SEM, result of this research prove that there is a positive and significant influence of those three factors on the quality of local government performance measurement. These findings provide practical contributions as a guide in improving the quality of performance measurement. Future research needs to expand the scope of the observation area, combine subjective and objective scales of the quality performance measurement variables, and develop other variables based on contingency, agency, and dynamic capabilities theory.